2020
DOI: 10.1101/2020.01.14.905851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Removable cranial window for sustained wide-field optical imaging in mouse neocortex

Abstract: A These authors contributed equally to this work Attempts to image neocortical regions on the surface of mouse brain typically use a small glass disc attached to the cranial surface. This approach, however, is often challenged by progressive deterioration in optical quality and permits limited tissue access after its initial implantation. Here we describe a design and demonstrate a two-stage cranial implant device developed with a remarkably versatile material, polydimethylsiloxane, which facilitates longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…While particularly suited to superficial tissues in dynamic and flexible locations, the versatility of PDMS makes our model readily adaptable for internal organ imaging by incorporating additional surgical steps for organ exposure or silicone-based glues. The suppleness of the device, however, renders it less suitable for implantation over rigid tissue sites, such as for brain or thoracic organ imaging that demands more specialist solutions ( 10 , 18 , 19 ). Nonetheless, silicone mass or surface modifications, in addition to drug embedding, can be used to alter the window’s mechanical, adhesive, or bioactivity properties for enhanced healing, tissue anchoring, permeability, and resistance to biological/chemical agents.…”
Section: Discussionmentioning
confidence: 99%
“…While particularly suited to superficial tissues in dynamic and flexible locations, the versatility of PDMS makes our model readily adaptable for internal organ imaging by incorporating additional surgical steps for organ exposure or silicone-based glues. The suppleness of the device, however, renders it less suitable for implantation over rigid tissue sites, such as for brain or thoracic organ imaging that demands more specialist solutions ( 10 , 18 , 19 ). Nonetheless, silicone mass or surface modifications, in addition to drug embedding, can be used to alter the window’s mechanical, adhesive, or bioactivity properties for enhanced healing, tissue anchoring, permeability, and resistance to biological/chemical agents.…”
Section: Discussionmentioning
confidence: 99%
“…The skull thinning procedure produced local heating, and surgeries are needed before every imaging experiment (Holtmaat et al, 2009). Although it was reported that craniotomy can potentially cause glymphatic dysfunction, gliosis, and changes in neurologic functions due to exposure infections and intracranial pressure imbalance (Plog et al, 2019), there are abundant evidences that craniotomy is safe for experimental animals (Askoxylakis et al, 2017;Cha et al, 2020). Based on a 3-month observation, the mice with the hidden cranial windows lived a normal life after the operations and had active physiological responses to external stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…While particularly suited to superficial tissues in dynamic and flexible locations, the versatility of PDMS makes our model readily adaptable for internal organ imaging, by incorporating additional surgical steps for organ exposure or silicone-based glues. The suppleness of the device, however, renders it less suitable for implantation over rigid tissue sites, such as for brain or thoracic organ imaging that demand more specialist solutions (10,18,19). Nonetheless, silicone mass or surface modifications, in addition to drug embedding, can be used to alter the window's mechanical, adhesive or bio-activity properties for enhanced healing, tissue anchoring, permeability and resistance to biological/chemical agents.…”
Section: Discussionmentioning
confidence: 99%
“…To address these limitations, here we developed a flexible and suture-less polydimethylsiloxane (PDMS)-based intravital imaging window dedicated to efficient, long-term maintenance at all body sites and improved animal welfare. While a few studies have reported the use of fixed-skull silicone membranes for brain IVM (18)(19)(20), the application of PDMS for soft tissue imaging remains unexplored, being limited to window designs that maintain the use of glass coverslips and sutures (21). As such, these models provide no benefit over conventional rigid windows.…”
Section: Introductionmentioning
confidence: 99%